Syariat in Action: Assessing the Impact of Jinayat Law on Social Order in Aceh - Bastiar Bastiar; Bukhari Bukhari; Anwar Anwar; Iswandi Iswandi; Mowafg Abrahem Masuwd (Justicia Islamica, 2025)
This research aims to examine in depth how the application of Qanun Jinayat in Aceh affects the dynamics of social order in the community. With a qualitative approach based on case studies, this study explores the perceptions of various community groups including religious leaders, law enforcement officials, and vulnerable groups to understand the effectiveness, challenges, and social impacts of the implementation of sharia-based law. Data was collected through in-depth interviews, field observations, and focus group discussions in four strategic areas of Aceh, and then analyzed thematically with the help of ATLAS.ti software. The results of the study show that although the jinayat law contributes to a reduction in moral offenses such as gambling and alcohol consumption, its implementation is not uniform and still faces various obstacles, both technical, social, and legal. Concerns about discriminatory treatment of women and minority groups are also a major concern. Therefore, it is recommended that there be harmonization between qanun and national law and the strengthening of protection for vulnerable groups, so that the application of this law can take place fairly and inclusive in order to maintain social stability in Aceh.